2020
DOI: 10.4142/jvs.2020.21.e77
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of virulence traits of Staphylococcus aureus isolated from bovine mastitis in semi-intensive and family dairy farms

Abstract: Background: Staphylococcus aureus is one of the main microorganisms that causes bovine mastitis, and its well-known virulence characteristics and interactions with the environment are used to aid the design of more efficient therapies. Objectives: To determine whether the virulence traits, such as antibiotic resistance and biofilm-forming and internalization abilities, of S. aureus isolated from bovine mastitis are related to dairy production system types. Methods: The study was performed in the Mexican states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Beyond antimicrobial resistance, the persistent mastitis associated with S. aureus is further linked to additional virulence factors that contribute to its pathogenicity and establishment within the mammary gland. These factors include its capacity to adapt and elude the host immune system, engagement in biofilm formation, and production of toxins, facilitating bacterial attachment and colonization [44][45][46]. Furthermore, the IR-BT technique was employed to assess the S. aureus isolates' relatedness for a more comprehensive understanding of the interrelation among them and their potential role in the infected cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond antimicrobial resistance, the persistent mastitis associated with S. aureus is further linked to additional virulence factors that contribute to its pathogenicity and establishment within the mammary gland. These factors include its capacity to adapt and elude the host immune system, engagement in biofilm formation, and production of toxins, facilitating bacterial attachment and colonization [44][45][46]. Furthermore, the IR-BT technique was employed to assess the S. aureus isolates' relatedness for a more comprehensive understanding of the interrelation among them and their potential role in the infected cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all 54 isolates showed the presence of the tetM gene, justifiable by their isolation performed at the same farm. Previously, the detection of both the tetK and tetM genes in NAS strains has been reported [40,41], as well as in S. aureus isolated from cows with mastitis [42].…”
Section: Discussionmentioning
confidence: 99%
“…It causes recurring and chronic infections and is highly resistant to β-lactam antibiotics. Its rate of resistance has dramatically increased in recent years [ 20 ].…”
Section: Introductionmentioning
confidence: 99%